2017
DOI: 10.1186/s12883-017-0945-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurogranin and tau in cerebrospinal fluid and plasma of patients with acute ischemic stroke

Abstract: BackgroundWhile neurogranin has no value as plasma biomarker for Alzheimer’s disease, it may be a potential blood biomarker for traumatic brain injury. This evokes the question whether there are changes in neurogranin levels in blood in other conditions of brain injury, such as acute ischemic stroke (AIS).MethodsWe therefore explored neurogranin in paired cerebrospinal fluid (CSF)/plasma samples of AIS patients (n = 50) from a well-described prospective study. In parallel, we investigated another neuronal prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 38 publications
8
68
1
2
Order By: Relevance
“…Furthermore, increase of oxidative or nitrosative stress, reduced antioxidant levels, and mitochondrial damage may also play major roles in the development and progression of AD [169]. Tau has been identified as a marker of poor outcome after stroke [170]. Its release may increase the excitotoxicity cascade through stimulation of glutamatergic receptors at the synapse and further progress neurodegeneration after stroke [171].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…Furthermore, increase of oxidative or nitrosative stress, reduced antioxidant levels, and mitochondrial damage may also play major roles in the development and progression of AD [169]. Tau has been identified as a marker of poor outcome after stroke [170]. Its release may increase the excitotoxicity cascade through stimulation of glutamatergic receptors at the synapse and further progress neurodegeneration after stroke [171].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…A previous study of 50 acute ischemic stroke patients reported that plasma t-tau levels peaked 7 days poststroke. 12 Moreover, higher plasma t-tau was related to greater stroke severity, poorer stroke outcomes, and larger infarct volumes. Thus, levels of plasma t-tau may increase in response to vascular brain injury and other brain insults.…”
Section: Discussionmentioning
confidence: 99%
“…There are robust indications that NF‐L, Tau, and GFAP levels in the CSF and in the blood are strongly correlated so that blood levels, easily accessible, could be used in the diagnosis of neurological disorders, making LP, with its inherent risks, unnecessary. A future confirmatory study in a population like ours should therefore contemplate investigating brain damage markers also in the blood.…”
Section: Discussionmentioning
confidence: 99%